An investigation of the effect of accessibility to General Practitioner services on healthcare utilisation among older people. (January 2019) - Mohan, Gretta; Nolan, Anne; Lyons, Seán
Abstract: Equity in access to healthcare services is regarded as an important policy goal in the organisation of modern healthcare systems. Physical accessibility to healthcare services is recognised as a key component of access. Older people are more frequent and intensive users of healthcare, but reduced mobility and poorer access to transport may negatively influence patterns of utilisation. We investigate the extent to which supply-side factors in primary healthcare are associated with utilisation of General Practitioner (GP) services for over 50s in Ireland. We explore the effect of network distance on GP visits, and two novel access variables: an estimate of the number of addresses the nearest GP serves, and the number of providers within walking distance of a person's home. The results indicate that geographic accessibility to GP services does not in general explain differences in the utilisation of GP services in Ireland. However, we find that the effect of the number of GPs is significant for those who can exercise choice in selecting a GP, i.e., those without public health insurance. For these individuals, the number of GPs within walking distance exerts a positive and significant effect on the utilisation of GP services. Highlights: Older people's physical access to General Practitioner (GP) services is examined. The number of local GPs influences visiting only for those who can choose a GP. A distance burden effect was not found in utilisation of GP care in Ireland. A proxy for workload of the nearest GP does not influence utilisation.